2023
DOI: 10.1186/s12889-023-15049-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in the associations between health literacy and problematic mobile phone use in Chinese middle school students

Abstract: Background Problematic mobile phone use (PMPU) is becoming increasingly popular and has serious harmful effects on physical and mental health among adolescents. Inadequate health literacy (HL) is related to some risky behaviors and mental health problems in adolescents. Nevertheless, few studies have explored the relationship between HL and PMPU and the gender difference in the relationship among Chinese adolescents. The aim of this study was to examine the associations between HL and PMPU and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Mental health literacy was assessed using an adolescent mental health literacy assessment scale developed by Chinese scholar Danlin Li [ 22 ]. This was based on a conceptual framework of mental health literacy and a theoretical model of knowing, believing, and acting, based on an extensive literature review, group discussions, and expert interviews.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health literacy was assessed using an adolescent mental health literacy assessment scale developed by Chinese scholar Danlin Li [ 22 ]. This was based on a conceptual framework of mental health literacy and a theoretical model of knowing, believing, and acting, based on an extensive literature review, group discussions, and expert interviews.…”
Section: Methodsmentioning
confidence: 99%
“…The scale was consistent with local Chinese cultural habits and had good reliability. It is widely used among Chinese high school and college students [ 22 , 23 ]. The Cronbach’s coefficient was 0.847.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the result revealed that gender, self-esteem and anxiety not the factors that contributes towards mobile phone usage among the university students. Eventually past studies indicated there have association between students and smartphone addiction (Li et al, 2023). Moreover, their study demonstrated male students were use mobile phone to access game apps and anxiety.…”
Section: Factors That Contributing In Influencing Mobile Phone Addict...mentioning
confidence: 98%
“…Nuestro estudio se desarrolla entre estudiantes, los cuales valoran su dependencia al móvil a través de un cuestionario, siendo un método ya empleado en otros estudios similares (Fekih-Romdhane et al, 2023;Li et al,2023). Ello permitirá diseñar un perfil de dependencia de los estudiantes universitarios al teléfono móvil y las redes sociales, identificándose posibles correlaciones entre distintas variables que pueden condicionar este uso, así como aportar conocimiento al debate de la posible consideración del uso abusivo de estas tecnologías como adicciones.…”
Section: La Vulnerabilidad De Los Jóvenes Al Uso Abusivo De Los Móvil...unclassified